Multilayer brain network modeling and dynamic analysis of juvenile myoclonic epilepsy - Ke, Ming; Wang, Changliang; Liu, Guangyao (Frontiers in Behavioral Neuroscience, 2023)
Multilayer networks, as mathematical extensions of traditional networks, are gaining popularity in neuroscience due to their ability to capture the full information of spatiotemporal datasets. This study used a multilayer network framework to analyse the changes in the structure of the brain community of juvenile myoclonic epilepsy (JME) patients from the perspective of dynamic analysis. First, functional magnetic resonance imaging (fMRI) data were collected from 35 JME patients and 34 healthy control subjects. In addition, the communities of the two groups were explored with the help of a multilayer network model and a multilayer community detection algorithm. Finally, differences were described by metrics that are specific to the multilayer network. Compared with healthy controls, JME patients had a significantly lower modularity degree of the brain network. Furthermore, from the level of the functional network, the integration of the default mode network (DMN) and visual network (VN) in JME patients showed a significantly higher trend, and the flexibility of the attention network (AN) also increased significantly. At the node level, the integration of 7 nodes of the DMN was significantly increased, the integration of 5 nodes of the VN was significantly increased, and the flexibility of 3 nodes of the AN was significantly increased. Moreover, through division of the core-peripheral system, we found that the left insula and left cuneus were core regions specific to the JME group, while most of the peripheral systems specific to the JME group were distributed in the prefrontal cortex and hippocampus. Finally, we found that the flexibility of the opercular part of the inferior frontal gyrus was significantly correlated with the severity of JME symptoms. Our findings suggest that the dynamic community structure of JME patients is indeed abnormal. These results provide a new perspective for the study of dynamic changes in communities in patients with JME.